Personal and contextual variables predict music consumption during the first COVID-19 lockdown in Canada - Dandiwal, Yuvika; Fleming, Lindsay; Levitin, Daniel J. (Frontiers in Psychology, 2023)
The COVID-19 lockdowns caused negative emotional consequences for people worldwide. The loss of routine, social interaction, and uncertainty left many feeling adrift and overwhelmed by anxiety and fear. Many employed coping strategies such as cleaning, dancing, and mindfulness-based practices to ameliorate negative emotions. Music listening was one of the most widely used coping strategies, moderated by personal and contextual variables. We obtained data from a Canadian national survey conducted in April 2020 to examine the role of personal (sex, age, education level, pre-pandemic income, minority status, feelings about music, and Schwartz’s “personal values”) and contextual variables (level of worry, changes to income, COVID-19 status and risk, having children at home, and internet access) in predicting music listening for stress relief, changes to music listening, changes to music watching, and music discovery during the first COVID-19 lockdown. Our results indicated that women, younger adults, individuals who like or love music, and those reporting high levels of worry were more likely to listen to music to relieve stress. Finally, personal variables were more significantly associated with music listening for stress relief than contextual variables.